2015
DOI: 10.1063/1.4938355
|View full text |Cite
|
Sign up to set email alerts
|

Selective transport of Fe(III) using ionic imprinted polymer (IIP) membrane particle

Abstract: The membrane particles was prepared from polyvinyl alcohol (PVA) and polymer IIP with weight ratios of 1: 2 and 1: 1 using different adsorbent templates and casting thickness. The permeability of membrane towards Fe(III) and also mecanism of transport were studied. The selectivity of the membrane for Fe(III) was studied by performing adsorption experiments also with Cr(III) separately. In this study, the preparation of Ionic Imprinted Polymer (IIP) membrane particles for selective transport of Fe (III) had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…It is seen that the PE IIP sequence of similarity is similar to that of the study using the PEGDE croslinker 8 . This is due to the large number of OH groups in the polymer causing less affinity for Cd and its greater affinity for Pb The results showed that the adsorption selectivity of Fe on Fe-Cr was higher than that of on Fe-Cd and Fe-Pb, with the a selectivity sequence Fe-Cr > Fe-Cd > Fe-Pb.…”
Section: Selectivity Of Metallic Ion Adsorptionsupporting
confidence: 60%
“…It is seen that the PE IIP sequence of similarity is similar to that of the study using the PEGDE croslinker 8 . This is due to the large number of OH groups in the polymer causing less affinity for Cd and its greater affinity for Pb The results showed that the adsorption selectivity of Fe on Fe-Cr was higher than that of on Fe-Cd and Fe-Pb, with the a selectivity sequence Fe-Cr > Fe-Cd > Fe-Pb.…”
Section: Selectivity Of Metallic Ion Adsorptionsupporting
confidence: 60%
“…make eugenol has potential as a selective compound carrier. Eugenol has been widely used for the separation of heavy metals, including eugenol polymer (polyeugenol) used to adsorb ion Fe (III) [5,6], as a functional polymer in membrane in situ [7] and in particles membrane [8,9]. Polyeugenol that has many OH groups (bases hard) has been researced the possibility of using as the carrier for separating metal ions Cr 3+ [10] and the carrier compound that has active group N derived from polyeugenol has selective towards metal ion Cu 2+ with percent transport 87, 54% [11].…”
Section: Introductionmentioning
confidence: 99%